ETIKA INTERAKSI SOSIAL DALAM POLA MEMINTA IZIN: Studi Analisis Surat al-Nūr - Abd Aziz (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2020)
This paper aims to describe the derivative of the explanation of Surat al-Nur in the form of social ethics in establishing interactions in the community. The method used is descriptive analysis of the pattern of asking for permission in Surat al-Nur. The finding in this paper is that the ethics of asking for permission is a form of respect and protection of one's privacy rights as a servant of Allah, which must be guarded. This social ethic is personal and communal in the midst of advances in knowledge and habits that are distorted by outside civilizations.